2006
DOI: 10.1111/j.1742-1241.2005.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure development after stroke

Abstract: Although there have been many studies on seizures following stroke, there is still much we do not know about them. In this study, we evaluated the characteristics of seizures in stroke patients. There were 2267 patients with a first-ever stroke, and after excluding 387 patients, 1880 were available for analysis. Of these 1880 patients, we evaluated 200 patients with seizures and 400 patients without seizures. We investigated the seizures according to age, gender, stroke type, the aetiology of ischaemic stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
34
5
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 34 publications
11
34
5
3
Order By: Relevance
“…No differences between age and gender were found between patients with and without ES. These data are consistent with those reported in previous studies (Reith et al 1997;Labovitz et al 2001), although age younger than 65 years and male gender have been shown to be a risk factors for ES in some other reports (Olsen et al 1987;Misirli et al 2006). Consistently with the most recent studies (Labovitz et al 2001;Lamy et al 2003), hypertension, diabetes mellitus, smoking, hyperlipidemia, ischemic heart disease, atrial fi brillation or previous TIA were not associated with ES.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No differences between age and gender were found between patients with and without ES. These data are consistent with those reported in previous studies (Reith et al 1997;Labovitz et al 2001), although age younger than 65 years and male gender have been shown to be a risk factors for ES in some other reports (Olsen et al 1987;Misirli et al 2006). Consistently with the most recent studies (Labovitz et al 2001;Lamy et al 2003), hypertension, diabetes mellitus, smoking, hyperlipidemia, ischemic heart disease, atrial fi brillation or previous TIA were not associated with ES.…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe an association between stroke etiology, particularly cardioembolic stroke, and the occurrence of ES. This is of interest as cardioembolic infarction has been a controversial risk factor for ES for years (Lesser et al 1985;Kittner et al 1990;Giroud et al 1994;Kraus et al 1998;Bladin et al 2000;Misirli et al 2006;So et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Young age was an associated factor in a retrospective study of 6044 patients with first or recurrent stroke and in a large, hospital-based, retrospective cohort study of 1880 patients with first stroke. 4,24 Conversely, the association of seizures with old age has been reported, for instance, in a retrospective population-based study of 675 British patients with a minimum follow-up of 2 years. 3 In relation to our findings, we propose that younger patients are more likely to experience large cortical infarcts rather than small vessel disease-related lacunar events, and that this may contribute to subsequent epilepsy development.…”
Section: Discussionmentioning
confidence: 99%
“…İleri yaşta epilepsi, (15,16). Yaşlı epileptiklerin etiyolojisinde ilk sırada SVH daha sonra nörodejeneratif hastalıklar, beyin tümörü, travma ve diğer nedenler gelmektedir (7,13).…”
Section: Discussionunclassified
“…Bulgularımız önceki çalışmaların sonuçlarına benzerdi (14)(15)(16)18). İnme sonrası kortikal etkilenme epileptik nöbetlerde belirli risk faktörü olmakla birlikte yapılan çalışmalarda sadece subkortikal tutulumun da nöbetlere yol açabildiği bildirilmiştir (16). Paradowski ve ark.…”
Section: Discussionunclassified